(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
This study examined the effect of milling parameters on the development of Ni/Al2O3 nanocomposites and refinement of NiO and Al powders. Ball milling of certain mixtures was followed by sintering at 800 and 1100 °C for 2 h. The X-ray diffraction results of the dry-milled powders indicated that increasing the ball-to-powder weight ratio from 20:1 to 42:1 produced finer particles, resulting in the synthesis of Ni/Al2O3 nanocomposites by milling at 200 rpm for 1.5 h. Extending the milling duration at lower rotational speeds yielded powders with nanoscale particle sizes. However, as observed under scanning electron microscopy and energy dispersive spectroscopy, a metallic matrix nanocomposite was formed via the mechanochemical reaction, and the crystallite size was estimated using the Williamson–Hall plot. Furthermore, using differential scanning calorimetry plots, we analysed the effect of milling on the temperatures of phase transformation and/or reduction reactions. The tribological performance of the developed nickel metal matrix composite was examined by employing a ball-on-disc tribometer at various load conditions. Indeed, the friction coefficient increases with applied forces and decreases with milling. Comprehensive examinations of the worn surfaces were conducted through the utilization of a scanning electron microscope and a 3D optical profiler.